2012
DOI: 10.1590/s0100-55022012000200002
|View full text |Cite
|
Sign up to set email alerts
|

Um estudo com egressos do curso de fisioterapia da Universidade Federal de Minas Gerais (UFMG): 1982-2005

Abstract: Estudo com egressos do curso de graduação em Fisioterapia da UFMG entre 1982 e 2005. Analisou-se a percepção dos egressos sobre o curso, bem como de seus percursos profissionais e as relações que podem ser estabelecidas entre ambos. Foi realizado um estudo transversal com questionário autoaplicável em egressos selecionados pelo método de amostragem estratificada, abordando os seguintes aspectos: identificação e contatos; estudos após a graduação; atividades profissionais; mercado de trabalho; avaliação do curs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
22

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 4 publications
(4 reference statements)
3
8
0
22
Order By: Relevance
“…This study showed the prevalence of female physical therapists in São Paulo (80%) (which is consistent with other studies 7,11,13,14,[17][18][19][20][21] ) and graduated after the year of 2001 in private institutions 19,22 . As the undergraduate program in physiotherapy lasts between 4 and 5 years, we expected the growth in the number of professional graduated after the year of 2001, reflecting the Higher Education Expansion plan adopted in 1997.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This study showed the prevalence of female physical therapists in São Paulo (80%) (which is consistent with other studies 7,11,13,14,[17][18][19][20][21] ) and graduated after the year of 2001 in private institutions 19,22 . As the undergraduate program in physiotherapy lasts between 4 and 5 years, we expected the growth in the number of professional graduated after the year of 2001, reflecting the Higher Education Expansion plan adopted in 1997.…”
Section: Discussionsupporting
confidence: 91%
“…This corroborates with the research carried out at the Federal University of Minas Gerais (83.8%) 14 , and is different from the profile of physical therapists of Santa Catarina, where 52.6% had performed some kind of specialization 7 . Career specialty areas are also in accordance with other studies 7,14,15 . In this study, we included aquatic physiotherapy as a specialty still not recognized due to the date of data collection, but it was already recognized by COFFITO 25 .…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations